Functional analysis of the most significant stock exchange characteristics-a case study of the Swiss stock exchange - Vesić Tamara; Đekić Marija; Zimonjić Stefan (Trendovi u Poslovanju)
The aim of this paper is to review transactions on the Swiss Stock Exchange and changes in key performance measurement indicators in the period of 2018-2019. Special attention is paid to the characteristics and functioning of the Swiss Stock Exchange and proving whether and to what extent the Swiss Stock Exchange functions in a different way from other world stock exchanges. The results indicate that it is necessary to have stable market movements in order to be able to have an adequately developed stock exchange (which is already known in the case of the Swiss financial system). Furthermore, most of the financial assets on the Swiss Stock Exchange are traded electronically and finally, current speculations about the existence of innovative approaches for the development of a cryptocurrency that will potentially be pegged to the franc (a certain "stable coin") were investigated.